Foundations of multimethod research synthesizing styles - Brewer, John, 1936-; Hunter, Albert (Thousand Oaks, [Calif.] ; London : SAGE, 2005)
'Foundations of Multimethod Research' offers an explanation of how a planned synthesis of various research techniques can be purposefully used to improve social science knowledge.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology